Successful Intracervical Insemination and Characteristics of Anoa (Bubalus sp.) Parturation Behavior in Captivity - . Judi; T L Yusuf; B Purwantara; D Sajuthi; M Agil; J Manansang; R Sudarwati; Y T Hastuti; B Huoso; A Widianti; S Prastiti (Media Peternakan, 2012)
Anoa, which is the endemic animal in Indonesia, its population is unevitably decreasing, therefore anoa included in the list of endangered species by International Union for Conservation of Nature (IUCN). The experiment was aimed to apply the artificial insemination (AI) technique for anoa and to examine their parturition behavior. The experiment involved 2 males and 5 females anoa at Taman Safari Indonesia Bogor. Semen was collected by electroejaculator, then evaluated and diluted in Tris-egg yolk extender. The anesthetized estrous females were inseminated intracervically with extended semen (100x106 sperm/1.0 mL). Females which did not show estrous signs during 2-3 cycles after AI were predicted pregnant, and therefore confirmed by ultrasonography. As a comparison, another predicted-pregnant female after natural mating was scanned. The results showed that intracervical AI resulted pregnancy in one female, and the gestation period of anoa was ranged from 313 d (AI) to 324 d (natural mating). There were three stages of parturition process was observed: Stage 1 was characterized by the abdominal contraction and amniotic membrane rupture, Stage 2 was characterized by the fetal expulsions, and Stage 3 was characterized by the placental expulsions and ingestion of placenta by the dam. The duration of each stage of parturition was 6-8 h (stage 1), 30-60 min (stage 2), and 15-180 min (stage 3). It is concluded that AI technique was applicable to anoa in captivity, and the parturation behavior of anoa was comparable to buffalo and cattle. However, the fetal delivery occurred when the dam was in standing position and the dam ingested the placenta.